1926-03: Digest Extension Service Newsletter, Auburn, Alabama, Volume 03, Issue 06 - Alabama Polytechnic Institute, Extension Service
This is the volume III, issue VI, March, 1926 issue of The Digest, a newsletter published monthly by the Extension Service of the Alabama Polytechnic Institute (now Auburn University). Some early issues are also published with the Experiment Station and the Agricultural College of the Alabama Polytechnic Institute. The newsletter includes articles of interest related to the Extension Service. Topics include general news, agriculture, agricultural extension work, home economics extension work, people, and research. This item has been aggregated as part of the Association of Southeastern Research Libraries (ASERL)'s "Deeply Rooted: The Agricultural & Rural History of the American South" project.Articles: Alabama farmers resolve to go forward; Something new; Pope Is a student; News in brief; The extension team of Macon County; As the editor sees it (editorial); Periods of chemistry; Late radio news; Vocational agriculture; Baby Is dead; I am the farmer; Teaching home improvement; Specialists look forward; Many 2-acre club boys; Personal news notes and comment; New county agents; Farmers plant lespedeza; Electrical meet is called; You may laugh; A school boy's essay on corns;